Influence of metallization process on solution-processed InGaZnO thin film transistors. (13th July 2021) - Kim, Byeongwan; Lee, Hyunkyung; Hong, Seungyeon; Kim, Hyo Jung; Kim, Kanghyun; Kang, Haeyong
Abstract: Low-temperature solution-processed InGaZnO (IGZO) thin film transistors (TFTs) have recently attracted significant attention as the next-generation flexible display TFTs, owing to their high transparency, high electrical performance, low-cost fabrication, and large-area scalability. However, solution-processed amorphous IGZO TFTs have several drawbacks, such as poor film quality or low stability, and have been studied with view to improving the device performance. One of the critical components determining device characteristics is the metallization process, which we systematically studied using aluminum (Al) source and drain electrodes. The electrical properties were measured for different channel lengths and evaluated using the threshold voltage ( V th ) and subthreshold swing (SS). Al electrodes directly affect the channel region, enhancing the electron density because of the doping effect from Al and oxygen vacancy-related oxidation of Al and causing an abnormal negative shift of V th, which is confirmed by the component analysis via various spectroscopies. To understand and improve the TFT characteristics, we conducted a low-temperature post-annealing process and polymer passivation and succeeded in moving V th from over 150 V to near 0 V and remarkably improved SS. This study discovered that the influence of source-drain metallization on the channel region determines the device characteristics through the close relation between metal oxidation and the number of oxygen vacancies.